2021
DOI: 10.24252/auladuna.v8i2a5.2021
|View full text |Cite
|
Sign up to set email alerts
|

Penerapan Media Komik Untuk Meningkatkan Kemampuan Literasi Dalam Memahami Soal Cerita Matematika Di Sekolah Dasar

Abstract: Penelitian ini berisi tentang kemampuan literasi matematika siswa dalam memahami soal cerita melalui penerapan media pembelajaran komik pada siswa SD Negeri 1 Karangtawang. Penelitian ini bertujuan untuk mendeskripsikan peningkatan kemampuan literasi matematika siswa dalam memahami soal cerita yang menggunakan media komik dengan siswa yang tidak menggunakan media pembelajaran komik. Subjek penelitian siswa kelas V berjumlah 39 siswa. Metode penelitian yang digunakan adalah eksperimen (quasi eksperimental desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
(11 reference statements)
0
2
0
2
Order By: Relevance
“…So, problem-based learning-based mathematics comics can support students' mathematical literacy abilities. This is reinforced by research conducted by Fitriyani et al (2021), which states that students who learn to use comic media in class can improve their mathematical literacy skills more than those who do not. Similar to the results of research by Rakasiwi (2019), which found that the effectiveness of comic media showed an increase in mathematical literacy skills, as seen from the increase in students' post-test results.…”
Section: Discussionmentioning
confidence: 99%
“…So, problem-based learning-based mathematics comics can support students' mathematical literacy abilities. This is reinforced by research conducted by Fitriyani et al (2021), which states that students who learn to use comic media in class can improve their mathematical literacy skills more than those who do not. Similar to the results of research by Rakasiwi (2019), which found that the effectiveness of comic media showed an increase in mathematical literacy skills, as seen from the increase in students' post-test results.…”
Section: Discussionmentioning
confidence: 99%
“…Hal ini memungkinkan pengelompokan cerita berdasarkan tema atau pesan moral, sehingga membantu orang tua dan pendidik dalam memilih konten yang cocok untuk usia dan kebutuhan anak(T1, n.d.) (Musyaffa et al, 2023). Selain itu, analisis genre juga berguna dalam mengidentifikasi kecenderungan dan kebutuhan yang belum terpenuhi dalam literatur anak (Safitri & Wulandari, 2023).…”
Section: Pendahuluanunclassified
“…The Judging from the application media, learning media in the comics form was very suitable to be implemented in developing the mathematical literacy of elementary school students in Indonesia (Fitriyani et al, 2021;Hasibuan et al, 2022). This happens because the learning characteristics of elementary school students who enjoyed illustrated stories make learning mathematics at the elementary school level fun and more meaningful (Fitriyani et al, 2021;Nurhasanah et al, 2020). Other results…”
Section: Mathematical Literacy Developmentmentioning
confidence: 99%